(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Studies on “identification of the sex from clavicle bone alone” are carried out by various workers all over the world.But, it is well known fact that the racial and geographical differences exist in the metrical measurement of all the bones including clavicles, as the determination of sex is a population specific phenomenon. Matrials and Methode : This study was conducted on100 male clavicles and 100 female clavicles collected from identified corpses brought for medicolegal autopsy at Department of Forensic Medicine Govt. Medical College Calicut. Measured the various parameters and compared with previous studies. RESULTS :In the present study, the length , midclavicular circumference and weight of male clavicles weres more than female clavicles. The female clavicle has its length around 86% of male clavicle and mean MCC around 83% of the male clavicles.. Robustness index also calculated, mean robustness index was 23.11, and could identify only 76 % males and 64% females by this. CONCLUSION:In order to establish the anthropometric standards, and for the evaluation of the same from time to time, the continuance of such studies in defined geographical areas over a particular period of time is needed.